الدراسة المقارنة عن الأصوات العربية عند اللغويين والقراء: Al-Dirāsah al-Muqāranah 'an Aswāt al-'Arabiyyah 'inda al-Lugawiyyīn wa al-Qurra' - Abrar, Muh.; Asriani, Asriani; Usman, Usman; Bugis , Manal (Diwan : Jurnal Bahasa dan Sastra Arab, 2024)
الهدف الرئيسي من هذه الدراسة النوعية هو فهم الظاهرة التي يدرسها الباحثون، كما أن القياسات المستخدمة في الظواهر الإنسانية، ومن بينها دقة المقياس الكمي المستخدم لقياسه، ستظل محتفظة ببعدها الكيفي. يحلل الباحثون على أن ذلك المصطلح العلمي فى علم الأصوات بخلاف مخارج الحروف دعوة إلى مقارنتها بعلم التجويد الذي يبحث فيه أيضا مخارج الحروف ولا سيما صفاتها. نظرا إلى حقيقة علم التجويد له نظام الأحكام يتكون على أحكام القراءة وكيفية القراءة ومخارج الحروف وصفاتها وأحكامها والمد ومقياس الطول وقصير القراءة المعينة وأحكام الأوقاف. وفى صفات الحروف مثلا فى علم الأصوات على أن القاف صوت قصي لهوي مهموي إنفجاري، فإحدى الصفات هي المهموس أوالهمس. اعترض الباحثون قليلا من الأمثلة المتعددة، والمختلة من جهة المخرج منها يوجد في علم التجويد بكون تقسيم المخرج على المخرج المحققي والمخرج المقدري، فهذا التقسيم لا يبقى فى علم الأصوات. ومن جهة الصفة منها يبقى فى علم الأصوات على سبيل الأصوات غير متضاد. وذلك لما فيها من الضعف والخفاء، وهذا البحث لا يوجد فى علم التجويد. الكلمات المفتاحية: اللغويين؛ القراء؛ الأصوات العربية This qualitative research is essentially to understand the apparent meaning of what the final and manufactured measurements were in their measurements, and will remain occupied with their qualitative dimension. When a person usually speaks, for example, the degree of satisfaction with work or the degree of satisfaction with a human group, phenomena that have mathematical measurements, then Al-Maiki analyzes the researcher on that scientific term in the science of phonetics other than the exits of the letters, an invitation to experiment with intonation through the science of intonation, in which the exits of the letters and their characteristics are also discussed . May God bless you, the manner and origins of the letters, their attributes, their rulings, the length, measuring length, reciting the rhombus, and the rulings on endowments. Among the characteristics of letters, for example, in phonology, there is a vowel in the vowel, so the two are technical, which are the whispered, or amos, if a little of the multiple choice is investigated, and the disordered in terms of the way out of them is found in the science of Tajweed, with the estimated way out, and this division does not exist in phonology. On the adjective side, there is in phonology, for example, non-antonymous sounds. This is because it contains weakness and failure, and this research does not exist in the science of Tajweed. Keywords: Linguist; Readers; Arabic Voices.